Modeling the structural equations of emotional divorce based on early maladaptive schemas, emotional empathy mediated by emotion regulation in married - Jalalvand, Mousgan; Navabinejad, Shokoh; Rezazadeh Bahadoran, Hamidreza; Khosravi babadi, AliAkbar (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to model the structural equations of emotional divorce based on early maladaptive schemas, emotional empathy mediated by emotion regulation in married women in Tehran. Methods: The study was a descriptive, correlational and statistical study of married women in Tehran. Using available sampling method, 200 married women living in Tehran were selected as a sample of friends and counselors of the Association for the Protection of Children's Rights online due to coronavirus. .The research instruments were Guttman (1999) Emotional Divorce Questionnaire, Young's maladaptive schemas (1998), Epstein and Mehrabian (1972) emotional empathy, and Gross and John (2003) emotion regulation. All analyzes were performed using SPSS26 and AMOS24 software. Bootstrap method was also used to analyze the intermediate relationships in MACRO Precruheiz (2008).. Results: The results of the direct effect showed that the schema of disconnection and rejection(β=0.343), Overvigilance and inhibition (β=0.294),has a positive and significant effect on emotional divorce, and emotional empathy (β= -0.345), has a negative and significant effect on emotional divorce. Also, the indirect effects of disconnection and rejection schemas (β=0.0320), Impaired Autonomy and performance(β=0.0447), Directedness (β= 0.0509), Overvigilance and inhibition (β=0.0628), impaired limits (β= 0.1252), and emotional empathy (β= -0.0140), on emotional divorce through emotion regulation were significant. The results showed that emotion regulation as a mediating variable could explain the relationship between maladaptive schema and emotional empathy. Conclusion: Since the findings of this study indicate strong and significant relationships between research variables and emotional divorce, it is suggested that through various means including mass media, daily hours to teach life skills, effective and positive strategies for emotion regulation and innovations to modify the schema. Initial incompatibilities should be considered and psychologists should be employed to discuss this issue.